Poetiks of L. Andreev’s play «The dog’s walse» - Сухоруков, Віктор Андрійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
In article is devoted to the thorough analysis of poetics and genre peculiarities of L. Andreev’s play « The dog’s walse ». The study showed that the important role in this work play modernistic principles of representation of world and person as neomythologism, intertextuality, motifity, dominating of symbolical types and characters, irony, grotesque. This is the “new drama” which moves behind the scene external conflict and the action, the key role is played by internal conflict and subtext, which is finding realization in neomifological storyline. The study of L. Andreev drama’s chronotop in various periods of his work, along with variability, demonstrates his apparent conceptual uniformity. The local framework, where he transfers the action in the play " The dog’s walse ", represents only spatial variations of the locuses of early dramas and plays of the second half of the 1900s, the invariant of which can be considered the room where the Life of Man flows in the work of the same name. Furthermore, in the play, aside from the spaceless chronotope offered to the spectator, it is steadily found, often dominating the open "space" chronotope, acquiring the symbolic spatial outlines of petersburg’s topos. In this regard, the transformation undergoes an author’s interpretation of the mythopoetic motive of the mask, which is an important attribute of the Andreev’s drama art system. Instead of sketchiness and hypertrophied mannequins, mask characters of the "conditional" drama came more deeply, at the level of subtext, grotesque images, in which the writer combines the motive of the mask with the motives of the game, duality, and again appeals to the traditional model of character of his mirrors for his work, which at different angles reflect not only the ideological doctrines and actions of the heroes, but also the state of their deformed consciousness and the psyche. The results of our research refute the conception, that approves the evolutional type of Andreev’s dramaturgy from early realistic to “conventional” symbolico-expressionistic drams and drams ‘panpsihe”. Type of the conflict, which lies in its basis, and also all levels of its structure revealed the modernistic nature and isomorphism with Andreev’s prose. Apparently, both in prose, and in dramaturgy of the writer there was no evolution, the accents in the author’s concept only changed and the appropriate art means and image forms merely varied. Already in the first dramas all was put that only came to light, deepened and became more obvious.